2020
DOI: 10.1155/2020/7352484
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Functional Ingredient Levan Synthesized by Bacillus siamensis Isolated from Traditional Fermented Food in Thailand

Abstract: The rising global population continues to threaten the world’s food security. The discovery of new technologies to produce food of nutritional and functional properties is urgently needed. One beneficial food to humans of known nutritional value is the prebiotic levan. To address the problem, the present work is aimed at isolating levansucrase enzyme-producing microorganisms from traditional fermented food in Thailand. Bacterial colony morphology was observed for mucoidal consistency on culture plates. Isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…fluorescens strain ES strain was isolated from soil in Egypt, in a previous study (unpublished) and proved to be capable of producing characteristic feature of mucoidal consistency when grown on sucrose medium since levan polymer usually obtained from sucrose-based substrates by different microorganisms ( Tomulescu et al, 2016 ). This characteristic feature of the colony could be attributed to the production of an extracellular levansucrase enzyme which is capable of converting sucrose in the screening medium to exopolysaccharides in the form of β- d fructoside (levan polymer) ( Thakham et al, 2020 ), Levansucrase enzyme biosynthesis have been reported to occur in many gram-negative and gram-positive bacteria ( Benkeblia, 2013 ). Jathore et al, 2012a , Jathore et al, 2012b reported the production of levan by P .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…fluorescens strain ES strain was isolated from soil in Egypt, in a previous study (unpublished) and proved to be capable of producing characteristic feature of mucoidal consistency when grown on sucrose medium since levan polymer usually obtained from sucrose-based substrates by different microorganisms ( Tomulescu et al, 2016 ). This characteristic feature of the colony could be attributed to the production of an extracellular levansucrase enzyme which is capable of converting sucrose in the screening medium to exopolysaccharides in the form of β- d fructoside (levan polymer) ( Thakham et al, 2020 ), Levansucrase enzyme biosynthesis have been reported to occur in many gram-negative and gram-positive bacteria ( Benkeblia, 2013 ). Jathore et al, 2012a , Jathore et al, 2012b reported the production of levan by P .…”
Section: Discussionmentioning
confidence: 99%
“…fluorescens levan. The obtained results, showed three different large and strong peaks at the Wavenumber of 2930 and 2885 cm −1 and particularly at 3394 cm −1 corresponding to the stretching vibration bands C—H aliphatic asymmetric and symmetric methyl and methylene, respectively which being conjugated with the C O groups because of intermolecular hydrogen bonding ( Thakham et al, 2020 ). Moreover, the observed band at the Wavenumber of 1650 cm −1 might correspond to the characteristic of the C bond, which could be related to uronic acid groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. siamensis was previously isolated in our laboratory from fermented soybeans and was found to produce levan at high sucrose concentrations [ 33 ]. B. siamensis is a gram-positive rod bacterium that belongs to the Bacillus genus, which has members found throughout nature.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study established that the isolated novel strain of Bacillus siamensis from fermented soybeans possesses biocatalytic properties and found to produce levansucrase. The B. siamensis strain produced a novel extracellular levansucrase for levan biosynthesis induced by using sucrose as the substrate [ 33 ]. With the aim to reduce production costs and to efficiently produce levan, the current study characterized the levansucrase enzyme produced by the novel strain of B. siamensis and optimized culture conditions for levansucrase production and levan biosynthesis.…”
Section: Introductionmentioning
confidence: 99%